Teoria i praktyka królewskiego wychowania na przykładzie eksperymentu edukacyjnego wiktoriańskiego księcia Walii - Misztal, Mariusz (Biuletyn Historii Wychowania, 2017)
For Queen Victoria and Prince Albert the proper education of their eldest son, and the future king of England, was of paramount importance. Their most important advisor in this matter was Baron Stockmar, who believed in strict control of every moment in the boy’s life. The article examines available documentary sources dealing with the theory of the prince’s education as presented mainly in Queen Victoria’s, Prince Albert’s and Stockmar’s memoirs, as well as the way this theory was translated into practice by the Prince’s tutors and teachers. The main documentary sources here are the official reports and private diaries of Lady Lyttelton, Henry Birch and Frederick Gibbs. All in all, to the great disappointment of the Prince’s parents, the educational theory promoted by Stockmar proved to be a complete failure.